First evaluation of the marine invasive species Spartina anglica as a potential renewable source of glycine betaine - Micheline Grignon-Dubois and Charffidine Echmak (Journal of Applied Pharmaceutical Science, 2013)
The invasive species, Spartina anglica C. E. Hubbard from Arcachon lagoon (common name English cordgrass) was evaluated for its glycine betaine (GB) content and compared with the native S. maritima. Seven collections were made over a 29-month period starting from January 2009 until May 2011. Aqueous methanolic extracts were prepared from both leave and rhizome tissue of the two species. Quantitative determination of the GB concentration in the crude extract was performed by 1H NMR, which offers a rapid and efficient way for precise determination of the amount of natural products in a single analytical step. The highest concentrations of GB were systematically found in S. anglica leaves, for which the GB content varied in the range 21.94-27.61 mg (gdw)-1 without apparent significant seasonal effects. The rhizome contents were notably lower 3.41-12.69 mg (gdw)-1, but remained of interest. Compared to sugar beet, which is the traditional resource of GB, the content of S. anglica was found up to 3 times greater. These values make S. anglica a raw material of interest for agricultural, dietary and pharmaceutical applications. The fact that S. anglica biomass may provide some economic benefits could help for developing future sustainable management plans of this worldwide invasive species.
Keywords: Spartina anglica, S. maritima, Glycine betaine, quan